THE LEADERSHIP OF KIAI IN SANTRIâ€™S LITERACY MANAGEMENT AT INTEGRATED ISLAMIC BOARDING SCHOOL USHULUDDIN SOUTH LAMPUNG AND ISLAMIC BOARDING SCHOOL HASANUDDIN BANDARLAMPUNG - Aulia, Afifah; Amiruddin, Amiruddin; Fauzan, Ahmad (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
The existence of pesantren doesn't have to be doubt. The great potential in education is such a hope for society and government. The dynamics of pesantren life with a dormitory system that lives under the guidance of the kiai for 24 hours a day should provide an advantage for the pesantren in terms of literacy culture compared to the Public Shool system. Therefore, the leadership of Kiai and the managerial system at Islamic boarding school is an interesting matter for research. The method of this research is descriptive qualitative method, Kyai and the caretakers of Islamic boarding school as the subject in this research. Â The result shows that the Kyai's leadership of the Ushuluddin Integrated Islamic Boarding School refers to legal-formal leadership, where the implementation of the leadership work mechanism applies institutional functions. Whereas, the Kyai's leadership of Pondok Pesantren Hasanuddin refers to religio-paternalistic leadership, where the interaction of the kiai with the santri or subordinates is based on religious values based on the leadership style of the Prophet Muhammad. Managerial Kiai adhere to the concept of general management, all seen in the literacy activity program and the performance of HR as a control measure for implementation in the field, although the stages and control methods are not clearly defined.